Keputusan Penggunaan Jasa Perbankan Syariah: Perspektif Nasabah Milenial - Syafrida, Ida; Aminah, Aminah; Awaludin, Taufiq (Universitas Islam Negeri Sunan Kudus, 2020)
This study aims to identify the party and the dominant aspects that influence millennial customers in using Islamic banking services and provide relevant recommendations. The research problem is because the role of Islamic banking has not been optimal in the national economy due to the low market share and small number of deposits. This is due to the low scale of the Islamic banking industry. Market share growth is also influenced by the growth in the number of Third Party Funds. To increase customer users, Islamic banks should innovate in knowing the needs, desires, tastes and behavior of customers so that they trust and be a loyal customers. One of the user segmentation is millennial society so this object research is millennial customer respondents. The research method is descriptive analysis, factor analysis and mean analysis. The results of study found that those who influence millennial customers in using Islamic banking services are majority on their own initiative. The dominant aspect that affects millennial customers in using Islamic banking services is the perception of reputation and the availability of networks and technology. The sub-aspect of the dominant perception of reputation is religious reputation or the principle of sharia conformity. The dominant aspect of network availability and technology is the availability of SMS/internet/online banking. Limitations of this study are related to the search for previous research literature that discusses respondents with millennial age segmentation is still few.